Comparison of Combustion Models for Lifted Hydrogen Flames within RANS Framework - Ali Cemal Benim (Energies, 2019)
Within the framework of a Reynolds averaged numerical simulation (RANS) methodology for modeling turbulence, a comparative numerical study of turbulent lifted H2/N2 flames is presented. Three different turbulent combustion models, namely, the eddy dissipation model (EDM), the eddy dissipation concept (EDC), and the composition probability density function (PDF) transport model, are considered in the analysis. A wide range of global and detailed combustion reaction mechanisms are investigated. As turbulence model, the Standard k-ε model is used, which delivered a comparatively good accuracy within an initial validation study, performed for a non-reacting H2/N2 jet. The predictions for the lifted H2/N2 flame are compared with the published measurements of other authors, and the relative performance of the turbulent combustion models and combustion reaction mechanisms are assessed. The flame lift-off height is taken as the measure of prediction quality. The results show that the latter depends remarkably on the reaction mechanism and the turbulent combustion model applied. It is observed that a substantially better prediction quality for the whole range of experimentally observed lift-off heights is provided by the PDF model, when applied in combination with a detailed reaction mechanism dedicated for hydrogen combustion.